Pelibatan Kelompok Masyarakat Kelurahan Bandar Lor Kota Kediri Pada Upaya Penyehatan Lingkungan - Forman Novrindo Sidjabat; Nining Tyas Triatmaja; Yoanita Indra Kumala Dewi (Universitas Pahlawan Tuanku Tambusai, 2021)
The waste problems in Bandar Lor include high piles of waste, the discovery of littered waste, and low waste processing activities, such as no waste sorting process before disposal (90.3%) and no waste recycling (94.7%) ). This community service aims to improve the knowledge and skills of the community in processing organic and inorganic waste with a target of 25 representatives of 5 RTs selected purposively, carried out in the form of lectures and demonstrations and carried out pretest and posttest activities which were tested using paired t-test. The result of this community service is an increase in the skills of participants, an increase in the average score of participants (pretest = 65.6 and posttest = 96.8), and this training activity has proven to be effective in increasing the knowledge and skills of the community to process organic and inorganic waste (p <0 , 05). This activity needs to get the support of the government by issuing an advisory to implement a culture of sorting and treating household waste Keywords: Environmental Health, Inorganic Waste, Organic Waste, Recycling